Effectiveness of Formal Mediation in Resolving Business Disputes - Asep Suryadi; Ridwan Hidayah (JURNAL AKTA, 2026)
This study aims to analyze the implementation of formal mediation in resolving business disputes and to examine its effectiveness in practice. The research uses a normative legal method with statutory and conceptual approaches through library research. The novelty of this study lies in the analysis of the operational procedures of formal mediation, including the registration process and implementation stages, as well as identifying the gap between legal norms and practical implementation. The results show that formal mediation has advantages such as faster resolution, lower costs, confidentiality, and the ability to maintain business relationships. However, its effectiveness is still limited due to low trust among parties, lack of legal awareness, and mediator competency issues. It is concluded that although formal mediation has strong legal foundations and high potential, its implementation is not yet optimal. Therefore, strengthening mediator capacity and increasing legal awareness are necessary to improve the effectiveness of mediation in business dispute resolution.